Investigating the Impact of Mergers and Acquisitions on Bidder Performance: The Evidence from China - Liu, Yufei (2015)
The development of mergers and acquisitions grows rapidly in Chinese market in recent years, but little study on Chinese M&A activities has been done. This paper is aimed to contribute the literature on M&A in China and examines 192 M&A transactions of Chinese public firms listed on Shanghai Stock Exchange during 2004-2013. From the event study analysis, the results show that generally there are significantly positive market reactions to the Chinese listed acquiring firms. The abnormal returns to acquirer at and a few days (1 day and 2 days) after the announcement of M&A are statistically significant and positive. Alternatively, we examine the sub-samples of different factors including method of payment, relative size, industrial relatedness, private/public target statue, book-to-market ratio and domestic/foreign target statue. Acquisitions of non-cash payment and acquisitions which acquire private target firms show significant positive returns to acquirer, low book-to-market acquirers seem to outperform the high book-to-market acquirers around the announcement of M&A. In addition, from the cross-sectional regression analysis, the result suggests significant negative impact of cash payment acquisition on return to acquirer around the announcement, while factors of book-to-market ratio and domestic target have relatively significantly negative influences on the acquirers’ performance during M&A activities.